Pengembangan Buku Saku Ekonomi Sebagai Media Pembelajaran Untuk Meningkatkan Motivasi Belajar Ekonomi Siswa - Nurjannah Nurjannah; Khairani Sakdiah (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2019)
Human Resources (HR) is to make humans become people who are faithful, independent, intelligent, advanced, skilled, knowledgeable, active, creative, responsible, and productive. So to realize it all needs a high learning motivation for students to be students who have high EQ and IQ. Motivation is one of the factors that can improve the quality of learning, because it will study seriously if it has high motivation (Mulyasa, 2012). To be able to learn well, a good process and motivation are needed. Someone does a business because of motivation. The existence of good motivation in learning will show good results (Sardiman, 2003). Therefore, teachers must be able to arouse student motivation so that they can achieve learning goals. One factor that is often considered to reduce motivation for learning is the subject matter itself and the teacher who delivers the learning material. So one effort or way to increase learning motivation can be attempted by using the learning strategies that are done, and on this occasion the researchers try to change the learning strategy by using learning media using pocket books. The purpose of this study is to create learning environments so as not to get bored and create comfortable learning conditions, so that it can increase students' learning motivation.